A gemini surfactant-containing system with abundant self-assembly morphology and rheological behaviors tunable by photoinduction. Issue 29 (30th April 2018) - Tu, Yan; Gao, Mengge; Teng, Hongni; Shang, Yazhuo; Fang, Bo; Liu, Honglai
Abstract : The photoisomerization of OMCA affects the degree of OMCA participation in the formation of mixed micelles and results in the transformation of micellar morphologies. Abstract : Photoresponsive micellar systems with adjustable aggregate morphologies and rheological properties may be useful in a number of fields such as in microfluidics, controlled release, and sensors. However, the complexity and great difficulty of synthesising photosensitive molecules hamper their practical applications to a significant degree. In this study, we constructed a novel photoinduced self-assembly system by introducing the photoresponsive derivative trans -2-methoxy-cinnamate ( trans -OMCA) into the gemini surfactant N, N ′-bis(dodecyldimethyl)-1, 2-ethane diammonium dibromide (12-2-12·2Br − ) solutions. The system displays abundant phase behaviors, and the long worm-like micelles, vesicles, as well as an aqueous two-phase system (ATPS) are observed in the 12-2-12·2Br − / trans -OMCA mixed system even at lower surfactant concentrations. The UV-responsive behavior of the formed vesicles and the worm-like micelles is investigated systematically. The results have shown that OMCA undergoes photoisomerization from the trans -form to the cis -form through UV light irradiation that alters the molecular packing at the micellar interface and thus leads to the transformation of micellar morphologies. The long worm-like micelles will turn into much shorter units when the sample is exposed to 365 nm UV light accompanied by a decrease in solution viscosity by more than an order of magnitude. The formed vesicle system, however, can be utilized to generate a multi-state self-assembly structure, including a worm-like micelle and a small spherical micelle, depending on the UV irradiation time. The morphologies of micelles in a 12-2-12·2Br − / trans -OMCA mixed system can be tailored by adjusting the system composition and the duration of UV light irradiation. Correspondingly, the rheological behavior of the 12-2-12·2Br − / trans -OMCA mixed system can be purposely tuned. The light-induced system with abundant self-assembly behaviors and tunable rheological properties would widen the potential application of gemini surfactants in drug delivery, smart fluids, and materials science.